Pengaruh Store Atmosphere, Lifestyle Dan Location Terhadap Keputusan Pembelian Di Masterpiece Coffe - Gian Ikmala Caesar; Zulkarnaen; Satriawan (Kredibel: Jurnal Ilmiah Manajemen, 2024)
The aim of this research is to find out how store atmosphere, lifestyle and location influence purchasing decisions at Masterpiece Coffee. The sample in the research was masterpiece coffee consumers, totaling 80 respondents. The analysis technique used is multiple linear regression analysis with the results Y = 0.686 + 0.368X1 + 0.350X2 + 0.436X3 calculated using the SPSS 25 program. From the results of the regression equation, it is found that store atmosphere has a significant effect with a regression value of 0.002 < an alpha value of 0.05, while the lifestyle test results have a regression value of 0.006 < an alpha value of 0.05. Finally, the location test results have a regression value of 0.002 < an alpha value of 0.05. These results show that store atmosphere, lifestyle and location influence purchasing decisions at Masterpiece Coffee both simultaneously and partially. In addition, dominantly, the results of the lifestyle test are the most dominant results of all test results, with a regression coefficient of 0.006 < 0.05. So, the conclusion in this research is that all variables, including store atmosphere, lifestyle and location, can increase customer purchasing decisions at Masterpiece Coffee Mataram.